Seasonal transformation and spatial variability of water masses within MacKenzie Polynya, Prydz Bay - Portela, E; Rintoul, SR; Bestley, S; Herraiz-Borreguero, L; van Wijk, E; McMahon, CR; Roquet, F; Hindell, M (Journal of Geophysical Research: Oceans, 2021)
We provide a detailed description of the spatial distribution, seasonality and transformation of the main water masses within MacKenzie Polynya (MP) in Prydz Bay, East Antarctica, using data from instrumented southern elephant seals. Dense Shelf Water (DSW) formation in MP shows large spatial variability that is related to the (a) local bathymetry, (b) water column preconditioning from the presence/absence of different water masses, and (c) proximity to the Amery Ice Shelf meltwater outflow. MP exhibits sustained sea ice production and brine rejection (thus, salinity increase) from April to October. However, new DSW is only formed from June onward, when the mixed layer deepens and convection is strong enough to break the stratification set by Antarctic Surface Water above and Ice Shelf Water below. We found no evidence of DSW export from MP to Darnley polynya, as previously suggested. Rather, our observations suggest some DSW formed in Darnley Polynya may drain toward the western Prydz Bay. Then, DSW is exported offshore from Prydz Bay through the Prydz Channel. The interplay between sea ice formation, meltwater input, and sea floor topography is likely to explain why some coastal polynyas form more DSW than others, as well as the temporal variability in DSW formation within a particular polynya.